Identification of Potential Biomarkers for CAD Using Integrated Expression and Methylation Data - Zhang, Xiaokang; Xiang, Yang; He, Dingdong; Liang, Bin; Wang, Chen; Luo, Jing; Zheng, Fang (Frontiers in Genetics, 2020)
DNA methylation plays an essential role in the pathogenesis of coronary artery disease (CAD) through regulating mRNA expressions. This study aimed to identify hub genes regulated by DNA methylation as biomarkers of CAD. Gene expression and methylation datasets of peripheral blood leukocytes (PBLs) of CAD were downloaded from Gene Expression Omnibus (GEO) database. Multiple computational approaches were performed to analyze the regulatory networks and to recognize hub genes, subsequently. Finally, top hub genes were verified in a case-control study, based on their differential expressions and methylation levels between CAD cases and controls. Totally 535 differentially expressed-methylated genes (DEMGs) were identified and partitioned into 4 subgroups. TSS200 and 5’UTR were confirmed as high enrichment areas of differentially methylated CpGs sites (DMCs). The function of DEMGs mainly enriched in processes of histone H3-K27 methylation, regulation of post-transcription and DNA-directed RNA polymerase activity. Pathway enrichment showed DEMGs participated in VEGF signaling pathway, adipocytokine signaling pathway and PI3K-Akt signaling pathway. Besides, expressions of hub genes fibronectin 1 (FN1), phosphatase (PTEN) and tensin homolog and RNA polymerase III subunit A (POLR3A) were discordantly expressed between CAD patients and controls, and related with DNA methylation levels. In conclusion, our study identified the potential biomarkers of PBLs for CAD, in which FN1, PTEN and POLR3A were confirmed.